Analisis Brand Equity Minuman Isotonik Pocari Sweat pada Konsumen Minuman di Pontianak - Hiong, Lauw Sun (MABIS, 2011)
Pocari Sweat Isotonic drink was first introduced in Indonesia in 1990 and distributed to Pontianak in 2006. Pocari Sweat which initially could not be accepted in the Indonesian market starts gaining its popularity. At present, the existence of high competition makes Pocari Sweat must be able to manage its brand to remain popular. The aim of this research was to analyse Pocari Sweat equity brand in terms of brand awareness, brand association, perceived quality and brand loyalty elements. This research used descriptive method. Data collection techniques used were observation, interview, questioner, and bibliography study. The number of samples in this research was 100 people using quota sampling method which used Slovin formula and purposive sampling with the respondents are those who have consumed Pocari Sweat at least three times, above 16 years old, and have ever consumed other brands isotonic drink. The technique analysis used was descriptive analysis, Cochran test, and Likert test.